The roles of health locus of control, epistemic beliefs,vaccination beliefs, cynicism – hostility, and chemophobiain decision-making regarding self-vaccination and vaccination of children - ДАНИЛЮК, Іван; ЛИТВИН, Сергій; ЯГІЯЄВ, Ілля; КУРАПОВ, Антон; МАЛИШЕВА, Каріне; ЛЬОШЕНКО, Олександра (Київський національний університет імені Тараса Шевченка, 2024)
Background. Vaccine hesitancy represents a significant challenge to public health, particularly in countries like Ukraine. This issue has been exacerbated by the ongoing military conflict, which has disrupted healthcare systems and increased societal stressors. Psychological factors such as chemophobia, health locus of control, epistemic beliefs, and vaccine conspiracy beliefs play pivotal roles in shaping attitudes toward vaccination. This study aims to identify the psychological and sociodemographic determinants influencing vaccination decisions in Ukraine, with a focus on self-vaccination and the vaccination of children. Methods. A cross-sectional survey design was utilized, involving 392 participants. Data were collected through online platforms, employing validated scales to measure chemophobia, health locus of control, epistemic beliefs, vaccine conspiracy beliefs, and cynicism-hostility. Vaccination attitudes and sociodemographic variables were also assessed. Statistical analyses included descriptive statistics, correlation analysis, generalized linear modelling (polynomial logistic regression), and mediation analysis. Results. Psychological antecedents of vaccination emerged as significant predictors of vaccination rates. Collective responsibility and confidence in vaccine safety positively correlated with the number of vaccinations received, while excessive calculation—characterized by critical information seeking—negatively impacted vaccination uptake. Chemophobia, although not a mediator between psychological antecedents and vaccination behavior, independently influenced lower vaccination rates. Epistemic beliefs were not associated with adult vaccination decisions but positively influenced decisions to vaccinate children. Sociodemographic factors, including gender, age, education, and religiosity, did not significantly predict vaccination behaviours. Conclusions. This study highlights the complex interplay of psychological factors in vaccination decision-making. Emphasizing collective responsibility and trust in vaccines could enhance public health campaigns, while addressing chemophobia through targeted education may help mitigate its negative effects.

Вступ. Наголошено, що вагання щодо вакцинації становить значний виклик для громадського здоров'я, особливо в таких країнах, як Україна. Ця проблема ускладнюється тривалим воєнним конфліктом, який порушив функціонування систем охорони здоров'я та посилив соціальні стресори. Психологічні чинники, такі як хемофобія, локус контролю здоров'я, епістемічні переконання та переконання щодо змови стосовно вакцинації, відіграють важливу роль у формуванні ставлення до вакцинації. Це дослідження має на меті визначити психологічні та соціально-демографічні детермінанти, які впливають на рішення щодо вакцинації в Україні, зокрема щодо вакцинації себе та своїх дітей. Методи. Використано крос-секційний дизайн дослідження за участю 392 респондентів. Дані зібрано за допомогою онлайн-платформ із використанням валідованих шкал для вимірювання хемофобії, локусу контролю здоров'я, епістемічних переконань, переконань щодо змови стосовно вакцинації та цинізму-ворожості. Також оцінено соціально-демографічні змінні в їх зв'язку зі ставленням до вакцинації. Для аналізу даних застосовано описову статистику, кореляційний аналіз, узагальнене лінійне моделювання (поліноміальну логістичну регресію) та медіаційний аналіз. Результати. Виявлено, що психологічні передумови вакцинації є значущими предикторами рівнів вакцинації. Колективна відповідальність та довіра до безпеки вакцин позитивно корелювали з кількістю отриманих респондентами вакцин, тоді як надмірна орієнтація на критичний пошук інформації негативно впливала на рівень вакцинації. Визначено, що хемофобія, хоча й не виступала посередником між психологічними передумовами та поведінкою щодо вакцинації, самостійно впливала на зниження рівнів вакцинації. Установлено, що епістемічні переконання не були пов'язані з рішеннями про вакцинацію дорослих, проте позитивно впливали на рішення вакцинувати дітей. З'ясовано, що соціально-демографічні фактори, такі як стать, вік, освіта та релігійність, не мали значного впливу на поведінку щодо вакцинації. Висновки. Висвітлено складну взаємодію психологічних чинників у процесі прийняття рішень про вакцинацію. Акцентовано, що колективна відповідальність та довіра до вакцин може покращити ефективність громадських кампаній у сфері охорони здоров'я, а цілеспрямована просвітницька робота може допомогти зменшити негативний вплив хемофобії.
Роль локусу контролю здоров'я, епістемічних переконань, переконань щодо вакцинації, цинізму – ворожості та хемофобії у прийнятті рішень щодо вакцинації себе та дітей
Keywords: vaccine hesitancy; chemophobia; health locus of control; epistemic beliefs; vaccine conspiracy beliefs; cynicism-hostility; вагання щодо вакцинації; хемофобія; локус контролю здоров'я; епістемічні переконання; переконання щодо змови стосовно вакцинації; цинізм-ворожість